A Study on the Properties of Self-compacting Concrete Using Ground Ferronickel Slag as a Supplementary Cementitious Material - Nuruzzaman, Md (Curtin University, 2023)
Self-compacting concrete (SCC) is a special type of concrete with some additional requirements beyond those of traditionally vibrated concrete, such as high flowability and consolidation by self-weight without any segregation of the ingredients. The study herein investigated the production of SCC by utilizing a metallurgical by-product, namely ferronickel slag (FNS), to enhance the green supply chain in the concrete industry. In this research, FNS was used at 40% replacement of natural sand and ground ferronickel slag (GFNS) up to 50% replacement of cement. Firstly, the pozzolanic activity of GFNS was evaluated to use it as a supplementary cementitious material and then by using both FNS and GFNS, the fresh, rheological, mechanical and durability properties of SCC were studied. The 7-day and 28-day strength activity index results (75.46–78.27%) are within the range that qualifies GFNS as a pozzolanic material. Again, the Frattini test validated marginal pozzolanic activity of GFNS at 8th day with clear pozzolanic activity at 15th day. The fresh properties, slump flow, T50, V-funnel, J-ring, L-box, U-box, visual activity index and V-funnel at 5 minutes, met the criteria of SCC recommended by European and Japanese standard. Rheological tests showed an increase in fluidity and improvement of workability of cement paste with the increase of GFNS. This is attributed to the delayed hydration of GFNS due to its low calcium content. The strengths showed a decreasing trend with increasing GFNS content. The 28 days compressive strength decreased from 79 MPa for the control mix by 16% due to 35% cement replacement by GFNS which is considered reasonable. Moreover, up to 35% replacement level, this study finds a compatible ITZ, with a thickness of around 55 µm. The elastic modulus and the hardness values from the nanoindentation test suggest a decrease of the calcium silicate hydrate with the increase of GFNS that decreased strength. XRD data confirmed this finding. The perm